An Epidemiological Study Of Hypertension Amongst Children From Various Primary Schools Of Surat City - Thakor H.G; Kumar P; Desai V.K (Wolters Kluwer Medknow Publications, 1998)
Research question: What is the prevalence of hypertension in school children aged 10 years and above? Objectives: 1. To find out the prevalence of hypertension. 2. To generate a profile of hypertensive cases. Study design: Cross-sectional. Setting: Selected primary schools run by Surat Manipal Corporation. Participants: School children aged 10 years and above. Sample size: 2250 children (1092 boys, 158girls) Study variables: Age, sex, body weight, body mass index Outcome variables: Prevalence of hypertension. Statistical analysis: X2 test Results: Overall prevalence of hypertension in children was 2.3 percent, separately in girls and 0.9 percent in boys. Body weight above 40kgms and body mass index (BMI) above 20 were differentiating points as children weighing more than 40kgms and/or with BMI more than 20 significantly higher prevalence of hypertension. Most of the cases were asymptomatic and also had no suggestive symptoms in the past.